A Case Report on Histiocytic Sarcoma: Lytic Lesion in Proximal Tibia - Desouza, Clevio; Nathani, Girish; Patil, Amol; Kale, Amit (Recent Developments in Medicine and Medical Research Vol. 14, 2021)
Introduction: Histiocytic Sarcoma is a rare neoplasm which causes less than 1 percent of all malignancies of hematologic origin. The biological behavior of this neoplasm resembles that of lymphoma, however its cell line is histiocytic and anon-lymphoid. Thereafter, the malignant cell of the histiocytic sarcoma shows morphological and immune-phenotypic characteristics of the histiocyte of mature origin. In the most recent 2016 revision, the WHO classified histiocytic sarcoma inside the macrophage along with other histiocytosis and stroma derived dendritic cell tumors. Case Report: A 70-year-old female with Histiocytic sarcoma of the left proximal tibia which presented as a solitary lytic lesion with pain in the left knee for 3 months. We here in describe a rare differential to a solitary lytic bone lesion without constitutional symptoms which was treated by our own conventional method. Conclusion: Though Histiocytic Sarcoma is a rare bony lesion; we should be aware of its presence and perform biopsy and immunohistochemistry in all lytic bone lesions. Conclusion: Though Histiocytic Sarcoma is a rare bony lesion; we should be aware of its presence and perform biopsy and immunohistochemistry in all lytic bone lesions.